Efektifitas Pembelajaran Kontekstual Berpendekatan Inkuiri Terbimbing Untuk Meningkatkan Kemampuan Literasi Sains Mahasiswa - Syafri Milanto; Nadi Suprapto; Mohammad Budiyanto (Postgraduate, University of Mataram, 2023)
This study aims to evaluate the effectiveness of contextual learning using guided inquiry to increase prospective physics teachers' scientific literacy skills. This study used the One Group Pretest-Postest design. Students in the physics education undergraduate program at Universitas Negeri Surabaya who took thermodynamics courses were the research subjects. The results showed that students' scientific literacy abilities before participating in the learning were already in a reasonably good category, and these students scientific literacy abilities experienced an increase after participating in contextual learning with a guided inquiry approach. The evaluation results of the n-gain test based on the pretest and posttest scores obtained an n-gain score of 0.64 or 64%. Accordingly, it can be concluded that contextual learning combined with the guided inquiry approach can effectively increase prospective teacher students' scientific literacy skills based on the evaluation results of the n-gain test